Marketplace Coverage During Pregnancy: What Can We Learn from State-level Variation? - Julia C P Eddelbuettel; Alison A Galbraith; Sarah Gordon; Anjali Kaimal; Laura F Garabedian (Health Affairs Scholar, 2026)
Abstract Introduction Little is known about the role of the Affordable Care Act Marketplaces in providing health insurance coverage for pregnant women. Methods Using PRAMS survey data from 2018-2019 from 36 states and Washington DC, we estimate the percentage of women with a pregnancy resulting in live birth who had Marketplace coverage during pregnancy, overall, by state, by Federal Poverty Level (FPL) categories, and by state-based versus federal Marketplace status. We also describe the preconception and postpartum insurance status and sociodemographic and health characteristics of pregnant Marketplace enrollees. Results 4.9% pregnant women had Marketplace coverage in 2018-2019. This percentage varied by state (1.6% in Iowa to 13.1% in Maryland) and was significantly higher in state-based Marketplaces vs. federally-run/facilitated Marketplaces (8.0% vs. 3.5%) and among premium subsidy-eligible women (i.e., <400% FPL). Pregnant Marketplace enrollees were more similar to pregnant women with Medicaid than those with private insurance in terms of sociodemographic characteristics and clinical predictors of adverse pregnancies outcomes. Conclusion Marketplace coverage is a small but important coverage source for women who had a live birth, insuring 1 in 20 women in our sample. The extent to which pandemic-era and recent policies affected Marketplace coverage of this population merits further investigation.